Spices research in India - PETER, K V (The Indian Journal of Agricultural Sciences, 2013)
Through concerted research in spices. 10 high-yielding varieties and hybrids in black pepper (Piper nigrum L.), 7 in cardamom (Elettaria cardamomum Maton), 2 in cinnamon (Cinnamomum zeylanicum Breyn.), 5 in ginger (Zingiber ofJicinale Rose.), 16 in turmeric (Curcuma domestica Valeton), 12 ’In corriander (Coriandrum sativum L.), 5’In cumin (Cuninum cyminum L.), 4 in fennel (Foeniculum vulgare Mill.) and 4 in fenugreck (Trigonella foenum-graecum L.) were recommended for release. Plant-propagation methods were standardized for nutmeg (Myristica fragrans Houtt), cinnamon, clove [Syzygium aromaticum (L.) Merr.], allspice [Pimenta dioica (L.) Merr.] and vanila (Vanilla planifolia Andr.). Tissue culture research especially for micropropagation and biotechnology in frontier areas of science are now being initiated. High production technologies for black pepper (Piper nigrum L.) and cardamom were formulated. Measures to manage Phytophthora foot rot in black pepper, rhizome rot and ’Katte’ in cardomom and soft rot in ginger were formulated and successfully transferred to farmers plots.